ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH DENGAN KEJADIAN HIV (+) PADA IBU HAMIL DI RSUD CILACAP PERIODE TAHUN 2013-2017 - ., Sohimah; Apriani, Evy (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
HIV/AIDS is a health problem in the world since 1981, this disease develops in a pandemic. HIV sufferers are usually difficult to distinguish from healthy people the incubation period of the HIV virus is for 10 years Depkes RI, 2006; Maryunani and Aeman, 2009). Based on information from the head of the VCT Cilacap Hospital that based on the existing data in the accumulation of the last 10 years there were 983 cases ofÂ  HIV / AIDS in Cilacap Regency and made Cilacap in third place in the Central Java Province. Of these 75% of people living with HIV / AIDS come from the productive age group between 25 and 49 years. Besides that based on the data available in April 2017 there were 7 (seven) pregnant women who were HIV positive. Based on the description above, it is important to conduct research on the characteristics of pregnant women with HIV at the Cilacap Regional General Hospital in the 2013-2017 period. The purpose of this study was to determine the analysis of factors related to the incidence of HIV (+) in pregnant women in Cilacap Regional General Hospital. Research conducted is descriptive research. The design used in this study using a method of using unpaired control cases, which aims to find the Analysis of Factors related to HIV (+) events in pregnant women. Data analysis in this study was conducted with Chi Square. The results of the reasearh were age factors and maternal occupational factors did not have a significant effect on the incidence of HIV (+) in pregnant women. Maternal education factors have a significant effect on the incidence of HIV (+) in pregnant women with a p value of 0.00 Key Word: Pregnant, HIV, Age, Education, Work